Application of Low Molecular Peptide-Based Biomarkers for the Rapid Identification of Echinochloa Species - Yoo, Sung Yung; Park, So Hyun; An, Jae Ho; Wankim, Tae (International Journal For Research In Agricultural And Food Science, 2019)
The objective of the present study was to determine the low molecular peptides in Echinochloa seeds as biomarkers for classification. Some peptide-based biomarkers for the classification of Echinochloa species were identified using SELDI-TOF, a mass spectrometry (MS) technique. Proteomic profiling using SELDI-TOF MS techniques could be a useful and powerful tool to discover peptide biomarkers and to discriminate and classify Echinochloa species, especially under 20 kDa. In 12 Echinochloa species, a total of 72 peptides were significantly detected on strong anion exchanger (CM10) and weak cation exchanger (Q10) arrays. Sixteen peptides on CM10 and 12 peptides on Q10 were selected as peptide biomarkers. The hierarchical heat map analysis of the peptide-based biomarkers indicated that Echinochloa species were classified into two groups and then more precisely subdivided. One major cluster group included early barnyard grass (ECOR), large barnyard grass (ECREC), jungle ricegrass (ECOLON), meadow barnyard grass (EPRAT), and barnyard grass (ECHCG). Hairless barnyard grass (ECGL), cockspur (ECRCR), awned billion-dollar grass (ECFRAW), awnless billion-dollar grass (ECFRAWL), awnless barnyard grass (EMITIS), awnless Japanese barnyard millet (EESCAWL), and awned Japanese barnyard millet (EESCAW) belonged to the other group.